Multi-year Satellite Observations of Sulfur Dioxide Gas Emissions and Lava Extrusion at Bagana Volcano, Papua New Guinea - McCormick Kilbride, Brendan T.; Mulina, Kila; Wadge, Geoffrey; Johnson, R. Wally; Itikarai, Ima; Edmonds, Marie (Frontiers in Earth Science, 2019)
Bagana, arguably the most active volcano in Papua New Guinea, has been in a state of near-continuous eruption for over 150 years, with activity dominated by sluggish extrusion of thick blocky lava flows. If current extrusion rates are representative, the entire edifice may have been constructed in only 300-500 years. Bagana exhibits a remarkably high gas flux to the atmosphere, with persistent sulfur dioxide (SO$_2$) emissions of several thousand tonnes per day. We have used satellite observations of SO$_2$ emissions and thermal infrared radiant flux to explore the coupling of lava extrusion and gas emission at Bagana. The highest gas emissions (up to 10 kt/day) occur during co-extrusive intervals, suggesting a degree of coupling between lava and gas, but gas emissions remain relatively high ($\sim$2500 t/d) during inter-eruptive pauses. These passive emissions, which clearly persist for decades if not centuries, require a large volume of degassing but non-erupting magma beneath the volcano with a substantial exsolved volatile phase to feed the remarkable SO$_2$ outgassing. The ability of this volatile phase to ascend freely to the surface is likely to be key to Bagana's largely effusive style of activity.